IMPLEMENTASI NILAI-NILAI PENDIDIKAN MULTIKULTURAL SEBAGAI KONSEP PEMBANGUNAN KARAKTER DALAM KELUARGA DI ERA REVOLUSI INDUSTRI 4.0 - Ansari Ansari; Raden Muyazin Arifin (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2020)
The values of multicultural education, in general, are four core values, among others: first, appreciation of the plurality of cultural reality in society. Second, recognition of human dignity and human rights. Third, the development of world community responsibilities. Fourth, the development of human responsibility and the strengthening of character in implementing universally, that is through the process of 5 phases of formation, namely: first, moral acting (good action) using habituation and culture. Second, to teach the knowledge of good values (moral knowing). Third, moral feeling and loving; Feel and love the good. Fourth, moral modeling of the surrounding environment. Fifth, repentance of all sins and things that are not beneficial can be (innocent) by carrying out the throne, Tahalli, and Tajalli. The 4.0 Industrial Revolution is a comprehensive transformation through the incorporation of digital technology and the Internet and the benefits that will be gained are enormous but at the same time, the impact it generates is also no less big. Therefore, the family plays an important role in the formation of personal and child development to achieve independence and optimal development in his life. So that the educative function in the family, socialization function of the community, protective function in the family, and the religious function of the family must introduce and instill religious values to the child.